Study of Reduced Graphene Oxide addition on the Electrical Conductivity and Flexural Strength of Metakaolin-based Geopolymer - Elsy Rahimi Chaldun; Andrie Harmaji; Nindya Kirana Prabaswari; Lina Nur Listiyowati; Achmad Subhan; Syoni Soepriyanto (Jurnal Keramik dan Gelas Indonesia, 2020)
Geopolymer with reduced Graphene Oxide (rGO) composite obtanined through Hummers method. This material is a substitute option for graphene because the nature of rGO is easier to produce in large quantities. In theory, it is expected that rGO can increase the flexural strength and electrical conductivity of geopolymer. The rGO composition used varies from 0-1 wt%. Geopolymer and their constituents were characterized by the Three Point Bending, EIS, SEM, FTIR, XRD, and XRF tests. Fly ash-based geopolymers have a flexural strength of 5.2 MPa at a composition of 0.5 wt% rGO, while metakaolin-based geopolymers with an addition of 0.25% rGO produce the highest flexural strength of 5.53 MPa. A frequency of 100,000 Hz tends to facilitate greater electrical conductivity, on fly ash-based geopolymers found electrical conductivity of 5.08 x 10-3 S / m, while for metakaolin-based geopolymers the electrical conductivity is higher ie 1.01 x 10-1 S / m.